P136 Asthma In Royal Air Force (raf) Personnel: Measuring Severity, Control And Previous Impact On Service Career. (10th November 2014) - Szram, J; Schofield, SJ; Mollan, IA; Davies, G; Bruce, D; Cullinan, P
Abstract : Background: The overwhelming majority of UK military recruitment occurs in the age group (18–24) in which the recent increases in childhood asthma have been greatest. Concerns about operational risks associated with asthmatic individuals are reflected in selection policies excluding applicants taking asthma treatment, reporting symptoms in the last five years or since the age of 16. This study was designed to characterise the severity and impact of asthma on current RAF serving personnel. Methods: Questionnaires were sent to all current service personnel with a diagnosis of asthma on their medical record; an equivalent number of non-asthmatic personnel (matched on age and sex) were also surveyed to provide a referent population. Information on asthma symptoms and treatment, reported change in deployment, medical fitness category and career intention was collected. Results: Of 463 asthmatics who responded to the survey, 167 (36.1%) were not currently on asthma treatment, 63 (13.6%) were on reliever therapy only and 233 (50.3%) were on regular asthma treatment. Two-thirds reported adult onset asthma. Those on regular treatment were more likely to have needed urgent/unscheduled treatment, been unable to work due to their asthma and have a current ACQ score indicating uncontrolled disease; whilst this group were more likely to be currently downgraded, they were no more likely to have returned early from deployment than those in other groups (Figure ). Comparing individuals with asthma and matched referents, those with disease were significantly more likely to be downgraded (OR 2.36 (95% CI 1.48–3.77), p < 0.001), prevented from deploying for medical reasons (OR 2.47 (95% CI 1.41–4.34), p = 0.006) and be assigned unfit (OR 1.79 (95% CI 1.20–2.73, p = 0.006)). Very few individuals had to return early from deployment, suggesting that restrictions were effective in mitigating risks posed by uncontrolled asthma. Conclusions: The findings from this cohort suggest that asthmatics in the RAF, particularly those taking regular treatment, are being restricted from some jobs and environments; this affects few individuals and does not appear to have a negative impact on service career. Decisions at recruitment are likely to have greater impact and would benefit from being studied prospectively. Abstracts M137 to M148 on page A212–218: